(De)marketing to Manage Consumer Quality Inferences. (February 2013) - Miklós-Thal, Jeanine; Zhang, Juanjuan
Savvy consumers attribute a product's market performance to its intrinsic quality as well as the seller's marketing push. The authors study how sellers should optimize their marketing decisions in response. They find that a seller can benefit from "demarketing" its product, meaning visibly toning down its marketing efforts. Demarketing lowers expected sales ex ante but improves product quality image ex post, as consumers attribute good sales to superior quality and lackluster sales to insufficient marketing. The authors derive conditions under which demarketing can be a recommendable business strategy. A series of experiments confirm these predictions.